PASIR PANTAI SELATAN JAWA TIMUR DALAM MORTAR - Siswoyo, M Pujo (Jurnal Teknik Sipil dan Perencanaan, 2009)
There were houses near to the beach, they were built with fine agregat around the beachbeside other materials. This paper discusses about compressing strength mortar containing coastalsand and river sand, with pozzolan portland cement (PPC) and portland cement (PC). The sandtook at the beach of at Pacitan, Tulungagung, Malang, Jember, and Banyuwangi. Sand observationwas taken place at laboratory of UMM. The specimens were cubical of 5 x 5 x 5 cm3. Mix design ofmortar were 1Portland Cement : 3 Fine Aggregate (sand of the beach-SB of 0, 20, 40, 60, 80,100% combined by river sand-RS of 100, 80, 60, 40, 20, 0%), there were two kind of cementPortland and Pozzolan Portland on that mixture, and the cement water ratio was 0,465. The resultshowed that finess modulus of beach sand were 2.34-3.52. The specific gravity of fine aggregatesof Puger beach was the greates of 2,873 gram/cm3 and the lowest was Sukamade beach sand of2,314 gram/cm3 , and Brantas river sand was 2,57 gram/cm3. The clay lump of sand took at Pugerbeach, Sukamade, Brantas river was 0.74, 0.76, and 0.68. The compressive strength on 14 daystest of control mortar of 1 PC : 3 river sand was 1.7% lower than mortar containing 20% of beachsand and 80% of river sand. The compressive strength of mortar 40% beach sand : 60% river sandand mortar with pure beach sand were 91% and 17% of the controll. On 28 days test showed thatcompressive strength of mortar of 1 PC : 3 of pure beach fine aggregates; 1PC:40% of beach sandand 60% river sand; 1PC:20% of beach sand and 80% river sand, were 16%, 75%, and 82% ofcompressive strength of normal mortar.Â Penelitian ini bertujuan untuk memberikan gambaran pemanfaatan pasir pantai sebagaialternatif bahan pengisi mortar. Penilaiannya dilakukan dengan membandingkan nilai kuat tekanmortar. Pengamatan di lapangan telah menunjukkan bahwa masyarakat pesisir pantai telahmenggunakan pasir pantai dalam mortar untuk membangun rumah atau bangunan lainnya. Pasirpantai diambil di : Pacitan, Tulungagung, Malang, Jember, dan Banyuwangi. Pemeriksaankarakteristik pasir dilakukan tanpa mencuci pasir. Perbandingan berat campuran mortar 1 semen :3 pasir, dengan faktor air semen 0,46. Jenis semen PC dan PPC, selanjutnya persentase pasirpantai menggantikan pasir sungai Brantas meningkat yaitu 100% pasir pantai (pp) : 0% pasirsungai (ps), 2) 80% pp : 20% ps, 3) 60% pp : 40% ps, 4) 50% pp : 50% ps, 5) 40% pp : 60% ps, 6)20% pp : 80% ps, dan 7) 0% pp : 100% ps; Faktor air semen 0,465. Spesimen berukuran 5x5x5cm3. Pengujian tekan mortar dilakukan pada umur spesimen 14 hari dan 28 hari. Hasilpemeriksaan menunjukkan bahwa butiran pp termasuk daerah 4, butiran ps Brantas diTulungagung daerah 1. Berat jenis ps 2,57 gr/cm3 , berat jenis pp Puger terbesar 2,873 gram/cm3dan terendah pp Sukamade yaitu 2,314 gram/cm3. Kuat tekan umur 14 hari kubus mortar ps lebihrendah 1,7% daripada mortar 20% pp : 80% ps, lalu kuat tekan rata-rata kubus mortar 40% pp :60% ps sebesar 91% dari kuat tekan mortar ps. Pada umur 28 hari, kuat tekan mortar ps memilikikekuatan tertinggi, selanjutnya menurun pada mortar 20% pp : 80% ps menjadi 82%, dan, menjadi75% pada mortar 40% pp : 60% ps Nilai kuat tekan terkecil adalah mortar pp sebesar 16% darikuat tekan mortar pasir sungai.